TO THE REVISION OF SOME JURASSIC GASTROPODS FROM CENTRAL RUSSIA: 1. GENUS PLICACERITHIUM - Guzhov A.V. (My University, 2002)
On the base of the protoconch structure, the subgenus Plicacerithium Gerasimov, 1992, of the genus Procerithium is reconsidered as a separate genus and moved from the family Procerithiidae to the family Epitoniidae. Several other genera from the Triassic and Jurassic are also assigned to the family for the first time, thus expanding the existing range of the epitoniids. The embryonic shells of three epitoniid species from the Jurassic of Central Russia are described for the first time. One new species, Plicacerithium altum, is described.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская